Climate change impact on streamflow and suspended sediment load in the flood-prone river basin - Rajesh Ranjan; Ashok Mishra (Journal of Water and Climate Change, 2023)
Understanding the relationship between climate change and changes in streamflow and suspended sediment load (SSL) at the regional scale is critical for future decisions on water resource management. Hence, this study assessed the projected climate change impact on streamflow and SSL based on CMIP6 projections in the flood-prone Mahanadi River Basin (MRB) using the SWAT model. Bias-corrected climate data from five global climate models under medium and extreme shared socioeconomic pathways (SSPs) were utilized as an input to the SWAT model for the baseline (1985–2014), near future (NF, 2020–2046), and mid future (MF, 2047–2073) periods. Rainfall is expected to increase by 2.86% (2.19%) and 13.35% (16.98%) in the NF and MF, respectively, under SSP245 (SSP585). Streamflow and SSL may increase by 6.38% (6.06%) and 4.43% (7.89%) in the NF and by 29.78% (36.90%) and 37% (46.43%) in the MF, respectively, under SSP245 (SSP585) scenario. Also, streamflow and SSL exhibited an increasing trend in most months as well as in most seasons. The findings may be helpful to decision-makers in identifying watershed management plans by offering more information on how climate change affects the hydro-sedimentological processes in a flood-prone river basin. HIGHLIGHTS Impact of climate change on streamflow and SSL in a flood-prone river basin is investigated by using CMIP6 projection.; Increases in rainfall and decline in the diurnal temperature range (DTR) in all the future scenarios are projected.; Streamflow and SSL are expected to increase in most months under medium and extreme scenarios.; Streamflow and SSL demonstrated an increasing trend in all the seasons except in summer.;